2011
DOI: 10.1038/aps.2011.145
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide induces cell-cycle arrest and apoptosis of human multiple myeloma cells in vitro via altering expression of histone demethylase LSD1 and JMJD2B

Abstract: Aim: To elucidate the relationship between triptolide-induced changes in histone methylation and its antitumor effect on human multiple myeloma (MM) cells in vitro. Methods: Human multiple myeloma cell line RPMI8226 was used. Apoptosis was evaluated using Annexin-V-FITC/PI-labeled flow cytometry, Hoechst 33258 staining, and transmission electron microscopy. Flow cytometry was used to detect the cell cycle distribution of the apoptotic cells. The presence of the LSD1, JMJD2B, H3K4me2, H3K9me2, and H3K36me2 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 52 publications
(62 reference statements)
3
34
0
Order By: Relevance
“…(TWHF), is a diterpene triepoxide with variety biological activities, such as anti-inflammatory, anti-cancerogenic, immunomodulatory and pro-apoptotic activities [1,2]. However, its potential toxicity to circulatory and reproductive system limits its clinical application [3].…”
Section: Introductionmentioning
confidence: 99%
“…(TWHF), is a diterpene triepoxide with variety biological activities, such as anti-inflammatory, anti-cancerogenic, immunomodulatory and pro-apoptotic activities [1,2]. However, its potential toxicity to circulatory and reproductive system limits its clinical application [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, curcumin (Yu et al, 2011;Li et al, 2013;Zhou et al, 2013;Yin et al, 2013) and triptolide (Kim et al, 2010;Liu et al, 2012;Wen et al, 2012) are able to potently inhibit the growth of human cancer cells in vitro and prevents tumor growth in vivo via inhibiting cell proliferation and inducing apoptosis. However, both of curcumin and triptolide possess side effects in high concentration (Banjerdpongchai et al, 2005;Clawson et al, 2010;Antonoff et al, 2010;Li et al, 2010;Borja-Cacho et al, 2010;Shakibaei et al, 2013;Du et al, 2013;Jiang et al, 2013).…”
Section: Combined Effects Of Curcumin and Triptolide On An Ovarian Camentioning
confidence: 99%
“…While, some research results found that TPL possibly played an important role in blocking protein synthesis and inhibiting cell proliferation by inhibiting the activity of RNA polymerase and affecting its transcription [5,10]. Specially, it was reported that TPL-induced cell apoptosis was possibly performed by cell cycle G1 phase arrest [11], but its mechanism is still unclear and remains to be elucidated [12]. To date, there is no biochemical changes information conceiving whether TPL induces cell cycle G1 phase arrest or not.…”
Section: Introductionmentioning
confidence: 99%